2016
DOI: 10.1093/molbev/msw012
|View full text |Cite
|
Sign up to set email alerts
|

p53mRNA and p53 Protein Structures Have Evolved Independently to Interact with MDM2

Abstract: The p53 tumor suppressor and its key regulator MDM2 play essential roles in development, ageing, cancer, and cellular stress responses in mammals. Following DNA damage, MDM2 interacts with p53 mRNA in an ATM kinase-dependent fashion and stimulates p53 synthesis, whereas under normal conditions, MDM2 targets the p53 protein for degradation. The peptide- and RNA motifs that interact with MDM2 are encoded by the same conserved BOX-I sequence, but how these interactions have evolved is unknown. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…There have been several attempts to solve the evolutionary history of the p53/p63/p73 protein family [ 6 , 13 – 15 , 20 ], but so far no phylogenetic tree, including both vertebrate and invertebrate species, has been published that agrees with the evolution of species. The phylogeny of MDM has been sparsely investigated, and the best published tree comprises only five vertebrates and three invertebrates species [ 23 ]. Due to less structural constraints, intrinsically disordered regions, like the p53/p63/p73 TAD, are allowed to substitute at a faster rate compared to structured regions [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been several attempts to solve the evolutionary history of the p53/p63/p73 protein family [ 6 , 13 – 15 , 20 ], but so far no phylogenetic tree, including both vertebrate and invertebrate species, has been published that agrees with the evolution of species. The phylogeny of MDM has been sparsely investigated, and the best published tree comprises only five vertebrates and three invertebrates species [ 23 ]. Due to less structural constraints, intrinsically disordered regions, like the p53/p63/p73 TAD, are allowed to substitute at a faster rate compared to structured regions [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors have suggested that preservation of not only the sequence but also the tertiary structure of this hairpin is crucial to maintain its function [37]. So far, there is no data concerning binding of Mdm2 to mouse p53 mRNA despite extended studies of Mdm2-p53 interactions using various cell cultures, invertebrates (C. intestinalis) [39] and mouse models [40]. Since our analyses reveled two potential different foldings of the C40 -C80 region of RNA-122 and RNA-247 we could envisage that Mdm2-mouse p53 mRNA interaction might be controlled by structural rearrangement of this region.…”
Section: Conservation Of Structural Elements Found In the 5′terminal mentioning
confidence: 99%
“…The interaction between the box-I p53 mRNA and MDM2 is also present in the pre-vertebrate Ciona instestinalis (109). The pre-vertebrate p53 RNA structure is regulated by temperature and the optimal binding temperature for the p53 mRNA–MDM2 protein interaction for C. intestinalis was measured at 18 and 30°C for the mammalian (107–109).…”
Section: Introductionmentioning
confidence: 99%